[BP.03.06] EFFECT OF COMBINED HORMONAL REPLACEMENT THERAPY ON THE ALDOSTERONE/RENIN RATIO IN POSTMENOPAUSAL WOMEN. (September 2017) - Ahmed, A.; Gordon, R.D.; Ward, G.; Wolley, M.; Mcwhinney, B.; Ungerer, J.; Stowasser, M.
Abstract : Objective: Plasma aldosterone/renin ratio (ARR) is the most popular screening test for primary aldosteronism (PA) is. Because both estrogen and progesterone affect aldosterone and renin levels, we studied effects of combined hormonal replacement therapy (HRT) on ARR, measuring renin as both direct renin concentration (DRC) and plasma renin activity (PRA). Design and method: 15 normotensive, healthy postmenopausal women underwent measurement (seated, midmorning) of plasma aldosterone, DRC, PRA, electrolytes and creatinine and urinary aldosterone, cortisol, electrolytes and creatinine at baseline and after 2 weeks and six weeks treatment with combined HRT (Premia 2.5 continuous). Results: Treatment with combined HRT was associated with significant increases in aldosterone [baseline median (range) 150 (85–600), 2 weeks 230 (129–790), 6 weeks 434 (200–1200) pmol/L (P < 0.001 Friedman Test)] and PRA [2.3 (1.2–4.3), 3.8 (1.4–7.0), 5.1 (1.4–10.8), P < 0.001]; but decreases in DRC [21 (10–31), 21 (10–39), 14 (8.0–30) mU/L, P < 0.01] leading to increases in ARR calculated by DRC [7.8 (3.6–34.8), 11.4 (5.4–48.5), 30.4 (10.5–90.2), P < 0.001]. The ARR calculated by DRC exceeded the cut off value (70) in two patients after 6 weeks. There were no significant changes in ARR calculated by PRA [79 (26–184), 91 (23–166), 88 (50–230), P = 0.282], plasma electrolytes and creatinine, and all urinary measurements. Conclusions: The combined oral HRT used in this study is capable of significantly increasing ARR with risk of false positive results during screening for PA, but only if DRC is used to calculate the ratio.